Case Report: Successful Management of a Compressive Intraspinal Coccidioides Species Granuloma in a Cat - Dowdy, Hannah; Evans, Jason E.; Jaffey, Jared A.; Wycislo, Kathryn L.; Struthers, Jason D.; Hostnik, Eric T. (Frontiers in Veterinary Science, 2022)
A 9-year-old, neutered male, domestic shorthair cat from Arizona, was presented for evaluation of a 7-day history of hind limb paraparesis that progressed to paraplegia. There was no history of respiratory abnormalities. Neurologic examination supported localization of a T3-L3 myelopathy. Computed tomography (CT) revealed an expansile widening of the spinal canal dorsal to L4 associated with a strongly contrast-enhancing mass. Moreover, CT series of the thorax revealed a diffuse miliary pulmonary pattern, as well as tracheobronchial, sternal, and cranial mediastinal lymphadenomegaly. Transthoracic lung lobe and sternal lymph node fine needle aspiration revealed pyogranulomatous inflammation with Coccidioides spp. spherules and endospores. A suspected diagnosis of spinal coccidioidomycosis was made; fluconazole (10.9 mg/kg PO q12h) treatment was initiated, and decompressive neurosurgery was performed. The granuloma was removed en bloc and histopathology revealed marked, chronic-active, pyogranulomatous myelitis with intralesional Coccidioides spp. spherules with endosporulation. Serum anti-Coccidioides spp. antibody titer results revealed a negative IgM and a positive IgG (1:4). The cat was treated with fluconazole for 445 days and examined at various time points, with the last examination 2 years after initial presentation. The cat returned to full ambulation with only mild functional deficits of the right hind limb. In conclusion, this report documents the diagnosis, treatment, and long-term follow up of a cat with a compressive Coccidioides spp. spinal cord granuloma. This case highlights the importance of including coccidioidomycosis as a differential diagnosis for cats with peracute hindlimb paraplegia that have lived in or traveled to regions where Coccidioides spp. is endemic, and demonstrates the potential for a good long-term outcome with decompressive neurosurgery and antifungal therapy.